introduction . Dalit Studies: New Perspectives on Indian History and Society - Ramnarayan S; Rawat and K Satyanarayana (Duke University Press, 2016)
In Dalit Studies Ed. by Ramnarayan S; Rawat and K. Satyanarayana Eds.(2016). Durham: Duke University Press, 2016